Cradle and all - Patterson, James, 1947- (Jimmy Patterson Books, 2016)
Anne Fitzgerald, a former nun turned private investigator, is hired by the Archdiocese of Boston to investigate two immaculate conceptions as terrifying forces of light and darkness gather.